Kegiatan Literasi Keuangan oleh OJK Kepada Perempuan di Riau Dilihat dari Sudut Pandang Teori Transmisi Pesan John Locke - Shanty Dewi Fauzy (Syntax Idea)
The low financial literacy index among the Indonesian population, as reflected in the 2022 National Survey of Literacy and Financial Inclusion (SNLIK), serves as the background for this literacy program. Women are identified as a priority group, aiming to make them financially literate, which, in turn, will have a positive impact on family finances and future generations. This research aims to contribute new insights into OJK's efforts to improve financial literacy among women in Riau using John Locke's message transmission theory as a theoretical framework. As the financial authority in Indonesia, OJK feels obligated to provide understanding and knowledge to Indonesian women to prevent various financial problems that may arise due to a lack of financial literacy. This study uses a literature review method to analyze the financial literacy efforts carried out by the Financial Services Authority (OJK) for women in the Riau Province on July 29, 2023. John Locke's Message Transmission Theory is employed as the theoretical framework, with the hope of revealing how OJK's financial literacy messages influence the knowledge, skills, and attitudes of the population, especially women, in managing their finances. This research is expected to contribute to a deeper understanding of message transmission in efforts to improve financial literacy in society, particularly among women.